2005
DOI: 10.1002/ca.20118
|View full text |Cite
|
Sign up to set email alerts
|

Cystic duct and Heister's “valves”

Abstract: The anatomy and physiology of the cystic duct have been relatively neglected by anatomists and the function of the spiral mucosal folds or "valves" of Heister, first described in 1732, remains obscure. The gross and microscopic anatomy of the cystic duct is reviewed together with results from laboratory investigations into the function of the cystic duct and its spirally arranged folds. The duct and spiral folds contain muscle fibers responsive to pharmacologic, hormonal, and neural stimuli. There is, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
(37 reference statements)
0
13
0
3
Order By: Relevance
“…During gallbladder refilling and emptying in response to hormonal and neural stimuli [45] , the bile flow passes through the cystic duct which connects the gallbladder and common bile duct, see Figure 1. Observations on the cystic duct anatomy have shown that the duct typically presents a combination of two types of structure: (1) in which the duct lumen wall may present the valve of Heister [46,47] ; (2) the duct has a smooth lumen which duodenum; (2) diverting hepatic bile into the gallbladder and (3) preventing reflux of duodenal contents from the duodenum into the biliary tree [61,62] .…”
Section: Geometry Of Biliary Duct and Flow Resistancementioning
confidence: 99%
“…During gallbladder refilling and emptying in response to hormonal and neural stimuli [45] , the bile flow passes through the cystic duct which connects the gallbladder and common bile duct, see Figure 1. Observations on the cystic duct anatomy have shown that the duct typically presents a combination of two types of structure: (1) in which the duct lumen wall may present the valve of Heister [46,47] ; (2) the duct has a smooth lumen which duodenum; (2) diverting hepatic bile into the gallbladder and (3) preventing reflux of duodenal contents from the duodenum into the biliary tree [61,62] .…”
Section: Geometry Of Biliary Duct and Flow Resistancementioning
confidence: 99%
“…Toj vo prosek e dolg od 2-4 cm, so kalibar od 1-5 mm. Negovata {uplina e reducirana so spiralni mukozni nabori opi{a-ni od Haister [1,2]. Anatomijata na vlivot-insercijata na DC vo дuktus хepatikus кomunis (DHK) e prika`ana vo сlika 1.…”
Section: Vovedunclassified
“…[irokorasprostranetiot i prifaten opis na anatomijata na еkstrahepati~noto бilijarno steblo e deka DC se vliva vo DHK vo sredinata na хepatoduodenalniot ligament, vo gornata tretina na DHK [1][2][3], iako postojat pove}e anatomski modeli koi spa|aat vo normalnata anatomija vo odnos na dimenziite i na insercijata na DC vo DHK [3][4][5]. Neprepoznaenite aberantni varijacii na DC, kako i konfuzijata-neprepoznavaweto na DHK mo`at da vodat vo seriozni komplikacii koga pacientot }e bide podlo`en na interventna radiologija ili hirurgija.…”
Section: Diskusijaunclassified
“…Manipulation of a catheter Into the cystic duct for successful intraoperative cholangiography can be made difficult by the tortuosity of the cystic duct and the spiral valves of Heister 1 . We describe a technique to eliminate these problems and allow successful positioning of the catheter within the cystic duct.…”
Section: Introductionmentioning
confidence: 99%